2022
DOI: 10.1002/ejoc.202201048
|View full text |Cite
|
Sign up to set email alerts
|

Latent Carbene: Diaminomethylation of Thiophenes

Abstract: The reaction of silylformamidine with various halo‐ and ethoxycarbonyl substituted thiophenes was studied. It proceeded via C−H bond insertion of the nucleophilic diaminocarbene that exists in an equilibrium with silylformamidine affording aminals. The reaction proceeded more readily at the 2(5)‐position compared to the 3(4) one. The number of halogens at the thiophenes markedly influences the reaction. The more halogens, the higher the reaction rate. Even one electron acceptor group at the thiophene ring is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Recently we have demonstrated that the thiophenes bearing at least one electron-accepting substituent also react with silylformamidine 1 . Taking into account the fact that 1 is tolerant to many functional groups, this approach can be used for the preparation of various thiophene carbaldehydes . Here, we continue our study of the reaction on the example of variously substituted benzenes in order to figure out the factors that affect the reactivity of the substrates and to establish the reaction mechanism.…”
Section: Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently we have demonstrated that the thiophenes bearing at least one electron-accepting substituent also react with silylformamidine 1 . Taking into account the fact that 1 is tolerant to many functional groups, this approach can be used for the preparation of various thiophene carbaldehydes . Here, we continue our study of the reaction on the example of variously substituted benzenes in order to figure out the factors that affect the reactivity of the substrates and to establish the reaction mechanism.…”
Section: Results and Discussionmentioning
confidence: 98%
“…Taking into account the fact that 1 is tolerant to many functional groups, this approach can be used for the preparation of various thiophene carbaldehydes. 11 Here, we continue our study of the reaction on the example of variously substituted benzenes in order to figure out the factors that affect the reactivity of the substrates and to establish the reaction mechanism. The introduction of acceptor groups into benzene moiety would make it more acidic and facilitate the reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we have also developed a simple two-step procedure for formylation of halogen-substituted thiophenes. [14] Given the reactivity of fluoropyridines and their multiple CÀ H bonds, the development of efficient and regioselective functionalization methods is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Recently we have presented silylformamidine 1 as a new perspective reagent that owing to an easy migration of the silyl group exists in an equilibrium with its carbene form 1′ (Scheme 1). [12] It reacts with various compounds via an insertion into C−H bonds giving aminals as products [12,13] . The mechanism and scope of the reaction has also been studied for the reaction of 1 with 1,3‐dihalobenzenes [13] .…”
Section: Introductionmentioning
confidence: 99%